The role of neoadjuvant therapy in pancreatic cancer: a review. (March 2016) - Russo, Suzanne; Ammori, John; Eads, Jennifer; Dorth, Jennifer
Controversy remains regarding neoadjuvant approaches in the treatment of pancreatic cancer. Neoadjuvant therapy has several potential advantages over adjuvant therapy including earlier delivery of systemic treatment, in vivo assessment of response, increased resectability rate in borderline resectable patients and increased margin-negative resection rate. At present, there are no randomized data favoring neoadjuvant over adjuvant therapy and multiple neoadjuvant approaches are under investigation. Combination chemotherapy regimens including 5-fluorouracil, irinotecan and oxaliplatin, gemcitabine with or without abraxane, or docetaxel and capecitabine have been used in the neoadjuvant setting. Radiation and chemoradiation have also been incorporated into neoadjuvant strategies, and delivery of alternative fractionation regimens is being explored. This review provides an overview of neoadjuvant therapies for pancreatic cancer.